Evaluating the effectiveness of the vehicle registration and licensing system of Botswana's Ministry of Transport and Communication using the Delone and McLean model - Laletsang-Mokokwe, Lebogang (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPhil)--Stellenbosch University, 2015.